Evaluation of anti-cancer activity on N-Substituted Tetrahydrocarbazoles - Subrahmanyam Lanka; Vaikuntarao Lakinani; Siva Rama Rao Kakani (International Journal of Pharmacy and Analytical Research, 2017)
A New series of N-Substituted Tetrahydrocabazole derivatives are prepared by cyclohexanone (1) treated with substituted phenyl hydrazine’s (2a, 2b) refluxed at 60°C for 10 mins undergoes cyclisation with the loss of ammonia, in presence of reagents like glacial acetic acid leads the formation of substituted tetrahydrocabazole (3a, 3b), this upon treating with 10% sodium hydroxide and substituted 4amino-benzoyl chlorides (4a, 4b) gives (4aminobenzoyl) 1, 2, 3, 4 tetrahydro carbazole derivatives. (5a, 5b). The structures of new derivatives should be purified by the different chromatographic techniques and assigned on the basis of 1H NMR, IR, and Mass spectral data. All the newly synthesized compounds were evaluated for their in-vitro anti-cancer activity.